The influence of individual and organizational factors on readiness to accept online learning among higher education lecturers in Nigeria - Ogbodoakum, Nnamdi; Mohd Ayub, Ahmad Fauzi; Zainal Abiddin, Norhasni (University of Hong Kong, 2022)
Information and communication technology have revolutionised many aspects of human interactions. One area which has received profound transformation is education and learning. Although technology-enhanced learning has widened access, and improved performance and quality; little has been achieved in many developing countries. The study is aimed at examining the predictors of readiness to accept online learning methods among faculty members (lecturers) in higher education institutions in Nigeria. Following the literature reviews, five factors (online learning attitude, online learning selfefficacy, management support, online content readiness and perceived benefit) were identified as the possible predictors of readiness to accept the online learning method. Using a sample of 277 valid respondents selected through proportional stratified sampling in 3 higher education institutions, it was found that online learning self-efficacy, management support, online content readiness and perceived benefit had statistically significant effects on readiness to accept online learning platforms among faculty members. Online learning attitude has no statistically significant effect on readiness to accept online learning methods. The study implies that faculty members (lecturers) who are confident in their ability to use the online learning method together with management support, institution E-content readiness and perception of benefit would accept the online learning method in teaching and learning.